For the love of physics : from the end of the rainbow to the edge of time-- a journey through the wonders of physics - Lewin, Walter H. G.; Goldstein, Warren (New York : Free Press, 2020)
Largely autobiographical account of the author's life as one who fell in love first with physics and then with teaching physics to students.
Includes index.
Keywords: Physicists -- Biography; College teachers -- Biography; Physics -- Study and teaching; Physics -- Study and teaching